2013
DOI: 10.2147/ppa.s28160
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety, efficacy, and tolerability of imidafenacin in the treatment of overactive bladder: a review of the Japanese literature

Abstract: Imidafenacin is an antimuscarinic agent with high affinity for the M3 and M1 muscarinic receptor subtypes and low affinity for the M2 subtype, and is used to treat overactive bladder. Several animal studies have demonstrated that imidafenacin has organ selectivity for the bladder over the salivary glands, colon, heart, and brain. In Phase I studies in humans, the approximately 2.9-hour elimination half-life of imidafenacin was shorter than that of other antimuscarinics such as tolterodine and solifenacin. Imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Intervention with such drugs may be useful for reducing nighttime voiding and several anticholinergic agents are currently available in Japan. Imidafenacin was released in Japan in 2007 [20,21]. It is more bladder-selective compared with other drugs [22], leading to mild anticholinergic adverse effects such as dry mouth and constipation [23], along with good long-term (52 weeks) efficacy, safety, and tolerability [24,25] in OAB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention with such drugs may be useful for reducing nighttime voiding and several anticholinergic agents are currently available in Japan. Imidafenacin was released in Japan in 2007 [20,21]. It is more bladder-selective compared with other drugs [22], leading to mild anticholinergic adverse effects such as dry mouth and constipation [23], along with good long-term (52 weeks) efficacy, safety, and tolerability [24,25] in OAB patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, the elimination half-life of imidafenacin (3.0 hours) is shorter than the elimination half-lives of other antimuscarinic agents. 21 The results from these studies have provided evidence that supports the efficacy, safety, and tolerability of imidafenacin in male LUTS patients with storage symptoms. In an effort to reduce storage symptoms without the severe AEs associated with anticholinergic agents and to compare studies of combination therapy involving low-dose anticholinergic agents, Bae et al, 9 and Kim et al 22 undertook studies and the results showed that combination therapy comprising low-dose propiverine improved the total IPSS and the storage symptom score, 9 and that compared with the standard dose, combination therapy comprising low-dose tolterodine had similar efficacy and safety profiles.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, imidafenacin displays greater selectivity for bladder tissue compared with salivary gland tissue . In addition, the elimination half‐life of imidafenacin (3.0 hours) is shorter than the elimination half‐lives of other antimuscarinic agents . The results from these studies have provided evidence that supports the efficacy, safety, and tolerability of imidafenacin in male LUTS patients with storage symptoms.…”
Section: Discussionmentioning
confidence: 85%
“…To confirm the efficacy of a particular drug, a study should determine whether the therapeutic agent is superior to a placebo and whether it is also not inferior to a pre‐existing drug. However, imidafenacin has already been reported to have significantly higher efficacy than placebos in both phase 2 and 3 trials,and these findings have been well‐reviewed …”
Section: Discussionmentioning
confidence: 99%